Pressure Load Characteristics of Nonideal Explosives in a Simulation Cabin - Chuan-hao Wang; Shu-shan Wang; Jing-xiao Zhang (Shock and Vibration)
In this study, an aluminum-containing charge was exploded in an enclosed simulation cabin to explore the characteristics of two types of damaging pressure loads formed by internal explosions: the first incident shock wave and the quasistatic pressure. A high-frequency piezoelectric sensor was used to measure the first incident shock wave and a low-frequency piezoresistive sensor was used to measure the quasistatic pressure. After obtaining effective experimental data, the experimental results were compared with the values obtained by the classical calculation model. The results show that the pressure loads generated by the internal explosions from the ideal explosive and the aluminum-containing explosive share similar load characteristics, given the same mass and benchmark explosive. The difference between the two explosives primarily lies in the amplitude of the load parameters. The aluminum-containing explosive has lower first incident shock wave and higher quasistatic pressure than that of the ideal explosive. For the peak overpressure of the first incident shock wave, the explosion shock wave load parameters of the aluminum-containing explosive, which are calculated based on the explosion heat theory, are higher than the measured values. The peak quasistatic overpressure is directly related to the total energy released by the explosion; however, they are hardly correlated with the reaction process. Therefore, the aerobic postcombustion reaction of the aluminum-containing explosive does not affect the analysis and calculation of the peak quasistatic overpressure. As a result, given the heat value of the explosive, the peak quasistatic overpressure of the explosive can accurately be obtained.